Automated Attendance Notifications and Parental Engagement: Evaluating a WhatsApp Gateway Information System in Islamic Boarding Schools - Safinah Safinah (Qualitative and Quantitative Research Center, 2026)
In faith-based residential institutions such as Islamic Boarding Schools, conventional manual attendance tracking frequently creates administrative latency, unmonitored absenteeism, and acute information asymmetries between school authorities and families. This study evaluates the operational implementation, socio-behavioral outcomes, and relational transformations catalyzed by an automated Radio Frequency Identification (RFID) and WhatsApp Gateway attendance information system in an Indonesian. Employing an explanatory sequential mixed-methods case study design, quantitative telemetry and longitudinal survey metrics were gathered via a total population census (N = 114 students and registered parents), integrated with 16 in-depth qualitative stakeholder interviews and observational audits. Server telemetry demonstrated a 94.0% message delivery success rate with a mean latency of 42.6 seconds. Inferential statistical analyses revealed significant behavioral adjustments, including an increase in mean daily attendance from 71.0% to 90.0% (p < 0.001), a reduction in undocumented absenteeism from 18.0% to 4.0% (p < 0.001), and a surge in active parental responsiveness from 34.0% to 88.0% (p < 0.001). Qualitative thematic synthesis indicated that real-time push notifications served as ambient behavioral nudges that dismantled truancy concealment while activating parental social capital. The study culminates in the Transparent Information System for Discipline (SITD) model, providing a validated, low-cost architectural blueprint that bridges technological automation with socio-technical safety nets to modernize educational governance and democratize school-family partnerships across the Global South.